KAJIAN YURIDIS TERHADAP PENEGASAN HIEARAKI PERATURAN PERUNDANG-UNDANGAN DI INDONESIA DALAM PERSPEKTIF STUFEN THEORIE - Muhammad Yusrizal Adi Syaputra (Universitas Medan Area, 2016)
Rule lower against the rules of higher then lower regulation it can test the material (judicial review) to be canceled entirely or partially canceled. The assertion of hierarchy intended to prevent overlap between legislation that could give rise to legal uncertainty. Position regulations set by the People's Consultative Assembly (MPR) House of Representatives (DPR), the Regional Representatives Council (DPD), the Supreme Court (MA), the Constitutional Court (MK), the Supreme Audit Agency (BPK), Commission Judicial (KY) , Bank Indonesia (BI), the Minister, the Agency, Organization, or commissions, in the Indonesian legal system recognized by Act No. 12 of 2011 either were born because of higher regulatory mandate and within the scope and authority of the minister. Thus, no doubt that the regulations set by state institutions, have binding force that must be obeyed by the parties set forth therein. While the Regulations issued policy also recognized as an Freies Ermessen in the execution of its duties and functions.